Solve the system by using elementary row operations on the equations. Follow the systematic elimination procedure.

3x1 + 6x2 = 6

4x1 + 7x2 = 11

Ok so first I multiply each entry in row 1 by 1/3 to get 1 in the first column in row 1.

Making it

1 2 2

4 7 11

Then I multiply by -4 and add to get row 2 column 1 to = 0

So

1 2 2

0 -1 3

Then I multiply each entry in row 2 by -1 to make it positive

there it's

1 2 2

0 1 -3

Now I multiply each entry in row 2 by -2 and add it to row 1 to make column 2 in row 1 a 0.

Now it's

1 0 -4

0 1 -3

x1 = -4

x2 = -3

3(-4)+6(-3) = -30

4(-4)+7(-3) = -37

Where did I go wrong? >.<